1994
DOI: 10.1017/s0950268800051293
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatitis C virus infection. A case-control study of blood donors in the Trent Region (UK)

Abstract: SUMMARYThe introduction of screening for hepatitis C virus (HCV) by the National Blood Transfusion Service identified donors who had acquired HCV infection. We undertook a case-control study amongst blood donors in the Trent Region to determine risks for HCV infection. A total of 74 blood donors confirmed positive for hepatitis C infection and 150 age, sex and donor venue matched controls were included in the study. Fifty-three percent of hepatitis C infected blood donors reported previous use of injected drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 22 publications
5
68
1
2
Order By: Relevance
“…The relative risk in people after acupuncture ranged between 1.9 (Michitaka et al, 1991) and 3.3 (Shin et al, 2000) and tended to increase with the increase in acupuncture sessions. No increased risk of HCV infection after acupuncture, however, was found in Japan, among atomic bomb survivors (Fujiwara et al, 2000), the United Kingdom (Neal et al, 1994) and the United States (Alter, 1999), though in Western countries the practice was seldom reported (Alter, 1999). The proportion of people with a history of acupuncture in our survey in South Korea (68%) is the highest reported so far in any study.…”
Section: Discussioncontrasting
confidence: 54%
“…The relative risk in people after acupuncture ranged between 1.9 (Michitaka et al, 1991) and 3.3 (Shin et al, 2000) and tended to increase with the increase in acupuncture sessions. No increased risk of HCV infection after acupuncture, however, was found in Japan, among atomic bomb survivors (Fujiwara et al, 2000), the United Kingdom (Neal et al, 1994) and the United States (Alter, 1999), though in Western countries the practice was seldom reported (Alter, 1999). The proportion of people with a history of acupuncture in our survey in South Korea (68%) is the highest reported so far in any study.…”
Section: Discussioncontrasting
confidence: 54%
“…A case-control study among British blood donors found that having been an HCW was a risk factor for having HCV infection (196). A number of case reports have documented occupational HCV transmission from anti-HCV-positive patients to HCWs in a variety of settings (234,263,268 Follow-up studies of HCWs who sustained percutaneous exposures to blood from anti-HCV-positive patients have found variable rates of HCV transmission (30,140,161,223,247,284).…”
Section: Risk Of Hcv Infection Postexposurementioning
confidence: 99%
“…For the analysis of potential risk facEnhanced surveillance of acute hepatitis B and C tors, a ranking of the known potential risk factors was determined based on currently available epidemiological information. This includes results from the Sentinel Health Unit Surveillance from 1993 to 1995 in Canada (Centre for Infectious Disease Prevention and Control, unpublished data), Centers for Disease Control and Prevention hepatitis surveillance report (14), and data in the epidemiological literature for hepatitis B (3,5,15) and hepatitis C (4,6,(16)(17)(18)(19), respectively. According to the ranking (see ordered lists of risk factors in the previous section), a case was assigned to a single risk factor category if the patient reported a history of such a risk factor in the six months before the onset of the disease, regardless of a history of other risk factors that were ranked lower than this risk factor in the ranking.…”
Section: Population Under Surveillancementioning
confidence: 99%